Indonesia's Diplomatic Maneuvers in the Current Geopolitical Situation - Yumetri Abidin; Irma Indrayani; Iskandarsyah Siregar (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Indonesia’s recent engagement with BRICS marked a strategic recalibration of its foreign policy amid intensifying great-power rivalries. Objective: This study aimed to examine how Indonesia employed a diplomatic hedging strategy to balance its relations with BRICS and the United States within an emerging multipolar world order. Methods: Using a qualitative research design that integrated document analysis and elite interviews, this paper analyzed Indonesia’s diplomatic discourse, policy statements, and trade relations during the 2022–2025 period. Results: The findings revealed that Indonesia’s multi-alignment behavior represented an adaptive evolution of its bebas aktif doctrine, emphasizing pragmatic engagement with competing powers while avoiding overdependence on any single bloc. This hedging behavior was manifested through selective economic cooperation, diversified partnerships, and cautious political signaling. Conclusion: This study contributed to the growing literature on middle-power diplomacy by offering empirical insights into Southeast Asia’s strategic autonomy under global systemic change. This paper argues that Indonesia’s multi-alignment policy strengthened regional stability while preserving strategic sovereignty within ASEAN’s centrality framework.